Research on Infrared Special Facula View Measurement Method Based on Image Processing Technology - Hanshan Li; Zhiyong Lei (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
In order to verify the detection range of special facula size which is emitted by infrared sensor, the method that uses image processing technology to calculate it parameters is proposed. According to the test condition, space geometric measurement model on calculating infrared sensor special facula view is set up, its measure principle is analyzed, and special facula image processing algorithm is give out. Standard grid screen is used to calculate and calibration special facula view, based on the size of special facula view in standard grid screen and the space geometric relation of camera and grid, the special facula view can be calculated and display in the computer. This paper analyzes the principle of measuring special facula view, researches its measure structure, and studies the disposing arithmetic of special facula view by image processing method, including image preprocessing, background and facula separation, and the edge detection. Using space physical geometric relation, special facula view angle can be gain. Through experiments, the technology of image processing is feasibility in special facula view calculating. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1396